Increased Age-Dependent Risk of Death Associated With lukF-PV-Positive Staphylococcus aureus Bacteremia. (5th December 2016) - Knudsen, Trine A.; Skov, Robert; Petersen, Andreas; Larsen, Anders R.; Benfield, Thomas; ,
Abstract: Background: Panton-Valentine leucocidin is a Staphylococcus aureus virulence factor encoded by lukF-PV and lukS-PV that is infrequent in S aureus bacteremia (SAB), and, therefore, little is known about risk factors and outcome of lukF-PV / lukS-PV -positive SAB. Methods: This report is a register-based nationwide observational cohort study. lukF-PV was detected by polymerase chain reaction. Factors associated with the presence of lukF-PV were assessed by logistic regression analysis. Adjusted 30-day hazard ratios of mortality associated with lukF-PV status were computed by Cox proportional hazards regression analysis. Results: Of 9490 SAB cases, 129 were lukF-PV -positive (1.4%), representing 14 different clonal complexes. lukF-PV was associated with younger age, absence of comorbidity, and methicillin-resistant S aureus . In unadjusted analysis, mortality associated with lukF-PV -positive SAB was comparable to SAB. However, lukF-PV -positive SAB nonsurvivors were significantly older and had more comorbidity. Consequently, by adjusted analysis, the risk of 30-day mortality was increased by 70% for lukF-PV -positive SAB compared with SAB (hazard ratio, 1.70; 95% confidence interval, 1.20–2.42; P = .003). Conclusions: lukF-PV -positive SAB is rare in Denmark but associated with a significantly increased risk of mortality. Although the risk of lukF-PV -positive SAB was highest in the younger age groups, >80% of deaths associated with lukF-PV -positive SAB occurred in individuals older than 55 years.